Pengaruh Penggunaan Model Pembelajaran Teams Games Tournaments (TGT) dengan Media Pembelajaran Game Fisika Asik (GASIK) terhadap Hasil Belajar Siswa SMP - Samsawati Samsawati; Muslimin Muslimin (Jurnal Kreatif Online, 2021)
The purpose of this study was to determine whether there was an effect of using the Teams Games Tournaments (TGT) learning model with GASIK learning media on the learning outcomes of junior high school students. This type of research was quasi-experimental with a non-equivalent pretest-posttest design. The population of this study was all eighth-grade students of SMP Negeri 10 Palu. The sampling technique used in this study was purposive sampling, with the research sample being 25 students of class VIII D as the experimental group and 24 students of class VIII E as the control group. The instrument of this research was a multiple-choice test. The learning outcomes test obtained showed that the average score of the experimental group was higher than the control group. Hypothesis t-test (two-tailed) obtained = 2.80 and 1.67 at the level of significance ⍺ = 0.05. This result means that the value of is outside the Ho acceptance area. So, it can be concluded that there is an effect of using the Teams Games Tournaments (TGT) learning model with GASIK learning media on the learning outcomes of junior high school students.